2010
DOI: 10.1176/appi.ajp.2010.09101476
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders and Suicide Among Young Rural Chinese: A Case-Control Psychological Autopsy Study

Abstract: Objective The authors examined the prevalence and distribution of mental disorders in rural Chinese 15–34 years of age who committed suicide. They hypothesized that mental illness is a risk factor for suicide in this population and that the prevalence of mental illness is lower in females than in males. Method In this case-control psychological autopsy study, face-to-face interviews were conducted to collect information from proxy informants for 392 suicide victims and 416 living comparison subjects. Five ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
153
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 34 publications
18
153
3
3
Order By: Relevance
“…The finding of a history of mental illness as an independent risk factor for suicide in our study is consistent with some studies in China [6,32,34] and Western countries [7,[54][55][56] . In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] .…”
Section: Issn 2372-5923supporting
confidence: 93%
See 3 more Smart Citations
“…The finding of a history of mental illness as an independent risk factor for suicide in our study is consistent with some studies in China [6,32,34] and Western countries [7,[54][55][56] . In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] .…”
Section: Issn 2372-5923supporting
confidence: 93%
“…The finding of a slight higher rate of suicide in males than in females is also consistent with other casecontrolled studies in China [4,6,34,42] although other studies in China reported that the rate of suicide in females was much higher than in males [3,36] . The cause of this "shift" toward a higher rate of suicide in Chinese male than in female remains yet to determine, but one possible reason is that the methodology using to identify suicide victims has become more complicate and thorough [4,6] .…”
Section: Issn 2372-5923supporting
confidence: 89%
See 2 more Smart Citations
“…Also, our strategy of scheduling interviews with proxy informants for suicide victims 3 to 6 months after suicide clearly differed from our strategy with informants for living control subjects and could increase the risk of recall bias. This is also a major challenge in other psychological autopsy studies of suicide (31,32).…”
Section: Limitationsmentioning
confidence: 99%